2013
DOI: 10.1161/circulationaha.113.004390
|View full text |Cite
|
Sign up to set email alerts
|

Atheroprone Flow Activation of the Sterol Regulatory Element Binding Protein 2 and Nod-Like Receptor Protein 3 Inflammasome Mediates Focal Atherosclerosis

Abstract: Athero-prone flow promotes inflammation in endothelial cells, and this process is critical for pathogenesis of many chronic inflammatory conditions such as coronary and carotid artery atherosclerosis, as well as abdominal aortic aneurysm. Signal mediators activated by athero-prone (disturbed) flow that have been described include NF-κB and protein kinase C, which is very different from athero-protective (steady laminar) flow1. In this issue a publication from Shyy’s lab shows the critical role of sterol regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…76 Indeed, other studies have found that inflammasome activation can occur in endothelial cells. 7779 However, in Chen et al’s study, the coronary lesions generated after LCWE injection were dramatically smaller than in our study, thus making comparison between the two studies difficult. 76 Additionally, they find evidence for active caspase-1 in the coronary ECs even under naive conditions, which is unusual considering that inflammasome activation is tightly regulated.…”
Section: Discussioncontrasting
confidence: 74%
“…76 Indeed, other studies have found that inflammasome activation can occur in endothelial cells. 7779 However, in Chen et al’s study, the coronary lesions generated after LCWE injection were dramatically smaller than in our study, thus making comparison between the two studies difficult. 76 Additionally, they find evidence for active caspase-1 in the coronary ECs even under naive conditions, which is unusual considering that inflammasome activation is tightly regulated.…”
Section: Discussioncontrasting
confidence: 74%
“…In terms of signal transduction, cholesterol depletion-activated SREBP2 showed anti-inflammatory action against excessive production of pro-inflammatory chemokines via EGR-1 and PPAR␥. However, in some studies, SREBP2 is a positive regulator of IL-8 expression by binding to a consensus sequence SRE located in the IL-8 promoter (Ϫ134 to Ϫ125) (32) and triggers IL-1␤-mediated inflammation via formation of NALP3 (NACHT, LRR, and PYD domains-containing protein 3) inflammasome (33). In contrast to these reports, SREBP2 activation did not contribute to transcription of chemokine expression in cholesterol-depleted enterocytes in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Human atheromata harbor activated inflammasomes (34). Other atherosclerosis-relevant stimuli that can augment inflammasome action include disturbed flow (such as prevails at sites of predilection to atheroma formation and complication) (35,36), and moderate hypoxia and acidosis (common in the core of plaques) (37,38). …”
Section: The Inflammasome Activates Interleukin-1βmentioning
confidence: 99%